2014
DOI: 10.1039/c3rp00155e
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying attitude to chemistry in students at the University of the South Pacific

Abstract: The attitude towards the study of chemistry for new entrant chemistry students from a multi-national, regional, tertiary educational institution in the South Pacific was investigated using a purpose-designed diagnostic instrument. The Attitude toward the Study of Chemistry Inventory (ASCI) was used to quantify attitude in a cohort of first year undergraduate (n = 144) and foundation (n = 108) chemistry students. A similar, generally positive attitude to the study of chemistry was shown by both groups of studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
(34 reference statements)
1
13
1
Order By: Relevance
“…Exploratory factor analysis of the data obtained using ASCI (Bauer, 2008) initially indicated latent factors which included intellectual accessibility (concordant with 'cognitive'), emotional satisfaction and anxiety (concordant with 'affective'). Further studies (Brown et al, 2014;Xu, Villafane, & Lewis, 2013) have confirmed this internal data structure, by consistently showing that both affective and cognitive sub-scales are contained within ASCI. Thus, we are confident that the instrument used to quantify attitude was appropriate and valid for this group of students.…”
Section: Discussionmentioning
confidence: 61%
“…Exploratory factor analysis of the data obtained using ASCI (Bauer, 2008) initially indicated latent factors which included intellectual accessibility (concordant with 'cognitive'), emotional satisfaction and anxiety (concordant with 'affective'). Further studies (Brown et al, 2014;Xu, Villafane, & Lewis, 2013) have confirmed this internal data structure, by consistently showing that both affective and cognitive sub-scales are contained within ASCI. Thus, we are confident that the instrument used to quantify attitude was appropriate and valid for this group of students.…”
Section: Discussionmentioning
confidence: 61%
“…One single item was independent of the other four factors and described with the term ‗Fear' (Bauer, 2008). This method became widespread and was used to evaluate the attitude of college-level students in the Pacific Islands towards Chemistry (Brown et al, 2014). In 2011, Bauer's method was refined by Xu and Lewis by reducing the number of items from its original 20-item form and five latent constructs to eight adjective pairs in two factors: -Emotional satisfaction‖ and -Intellectual accessibility‖ (Brandriet et al, 2011;Xu and Lewis, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…ASCI was originally validated in the US with undergraduates majoring in chemistry [9], and subsequently, a shorter version of the original 20 item questionnaire was developed by [10], also in chemistry undergraduates. The Attitude toward the Subject of Chemistry Inventory (ASCIv1) developed by [9] to measure student attitudes toward chemistry as a discipline was recently used to quantify chemistry attitudes of college level students in the Pacific Islands [11]. This shortened version (ASCIv2) has been used in Australia and the US [12], and contains eight items in two subscales, 'intellectual accessibility' congruent with the cognitive component of attitude, and 'emotional satisfaction' congruent with the affective component of attitude.…”
Section: Introductionmentioning
confidence: 99%